2017
DOI: 10.3906/biy-1703-101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of celecoxib and L-NAME on apoptosis and cell cycle ofMCF-7 CD44+/CD24–/low subpopulation

Abstract: IntroductionBreast cancer is the primary cause of death in malignancies among females (Regulski et al., 2016). It is suggested that a major population of breast tumor was incapable of further growth but only a minute fraction was able to seed new cancers, called cancer stem cells (CSCs) (Al-Hajj et al., 2003). During recent years, studies have identified CSCs as the subpopulation of tumor cells with a unique capacity for self-renewal and the ability to give rise to a heterogeneous population of cancer cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…MTT assay was employed to study the cytotoxic effect of free drug, blank nanocarriers, and drugloaded nanocarrier 111,112 . 10 4 cells of MCF-7 were cultured on each well of 96-well plates and were incubated for 24h.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…MTT assay was employed to study the cytotoxic effect of free drug, blank nanocarriers, and drugloaded nanocarrier 111,112 . 10 4 cells of MCF-7 were cultured on each well of 96-well plates and were incubated for 24h.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…IC50 was determined as being 12.2 mM in DU145 cells. Majdzadeh et al 27 studied the effect of L-NAME on MCF-7 breast cancer cells and their IC50 was between 10 mM and 20 mM in the MTT test. In their study, the viabilities of MCF-7 cells at 10, 20, and 40 mM of L-NAME were nearly 80%, 40%, and <20%, while in the current study, the viabilities of DU145 cells at 8, 16, and 32 mM of L-NAME were 68.4%, 33.3%, and 12%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we detected a dose-dependent rise in apoptotic markers and also confirmed this result by morphological analysis. In literature, in the study of Majdzadeh et al, 27 L-NAME was suggested to partially lead to apoptosis and proposed to show its effect by another cell death mechanism. In our study, we found increase in CASP3, CYCY, and Bax immunostaining as well as apoptotic hallmarks morphologically.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 33–36 ] evaluated the impact of celecoxib on various cancer cell lines to determine their sensitivity to celecoxib alone or in combination with other anticancer agents. For instance, El‐Awady et al [ 34 ] stated the concentration‐dependent effect of celecoxib on five cancer cell lines (HeLa, HCT116, HepG2, MCF‐7, and U251).…”
Section: Celecoxib As Anticancer Agentmentioning
confidence: 99%